Media programming : strategies and practices - Eastman, Susan Tyler; Ferguson, Douglas A. (Wadsworth, Cengage Learning, 2013)
"This book about media programming deals with both the structured and unstructured media. By structured we mean the traditional mass communication media of broadcast television and radio and the cable networks. ... By unstructured we mean the parts of the huge online world that carry old and new television programs and radio shows, talk and music that come via the web to your laptop or tablet or cell phone--or perhaps your TV set."--Pref